EMPLOYEE EFFICIENCY AND FIRM’S BUSINESS PERFORMANCE: EVIDENCE FROM QUOTED CONSUMER GOODS COMPANIES IN NIGERIA (World Bulletin of Social Sciences, 2023)
This study investigates effects of employee aggregate efficiency on firm’s business performance in Nigeria, using a three panel data models, namely; pooled regression, fixed and random effects models. The data consists of 10 selected companies that are listed on the consumer goods index of the Nigerian stock exchange NSE, covering a period of seven years (2007 to 2013). Data were sourced and computed from selected companies annual report and are analysed in Eviews 7 version. Return On Equity (ROE) serves as proxy for firm business performance, while revenue per employee, staff costs and directors emoluments are dimensions of employee efficiency. When fixed effects estimates were compared with random effects estimates, there is strong evidence that the unobserved firm-specific effects are correlated with that of firm’s revenue per employee, staff costs and directors emoluments. The study found staff costs and financial performance to be negatively related. This implies that an increase in staff costs would lead to a decrease in the firm financial performance. Also, there is weak evidence that directors’ emoluments and firm’s financial performance are positively related. This means an increase in directors’ emolument would lead to an increase in firm’s financial performance. However, there is no evidence that revenue per employee can significantly influence firms’ financial performance. Overall, about 83% of the changes in firms’ financial performance can be significantly explained by joint influences of revenue per employee, staff costs and directors’ emolument. It is therefore recommended that firms desiring to improve business performance should increase efficiency and productivity through directors’ remuneration optimization of employee performance inclusion.
Keywords: Employee aggregate efficiency; business performance; pooled OLS model